The Influence of Green Product, Green Brand Image, and Green Advertising on Le Minerale Product Purchase Preferences among Binjai City Residents . - Try Andini, Febrianty; Rokan, Mustapa Khamal; Dharma, Budi (Yayasan Sinergi Kawula Muda, 2025)
ABSTRACT: The purpose of this study was to determine how consumer preferences for mineral products in Binjai City, North Sumatra, are influenced by green products, green brand images, and green advertising. Quantitative analysis used responses obtained from a random stratified sample. The low R Square of 29.4% was due to momentum, which resulted in bias in purchase preferences during the data analysis process. The study findings showed that green products were positively and significantly related to the intention to purchase mineral products, green illustrations were positively and significantly related to the intention to purchase mineral products, and green advertising was positively and significantly related to the intention to purchase mineral products. In addition to using green products, green brand images, and green advertising, green marketing should always be carried out. Keywords: Green Advertising; Green Brand Image; Green Product; Purchase Preferences